2012
DOI: 10.1111/j.1349-7006.2011.02197.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TLAK cell‐originated protein kinase predicts poor prognosis in patients with stage I lung adenocarcinoma

Abstract: Tumor recurrence is the most common cause of disease failure after surgical resection in early-stage lung adenocarcinoma. Identification of clinically relevant prognostic markers could help to predict patients with high risk of disease recurrence. A meta-analysis of available lung adenocarcinoma microarray datasets revealed that T-LAK cell-originated protein kinase (TOPK), a serine/threonine protein kinase, is overexpressed in lung cancer. Using stable cell lines with overexpression or knockdown of TOPK, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 45 publications
(99 reference statements)
7
41
0
Order By: Relevance
“…These results are similar to those reported by Shih et al . Wei et al . found that overexpression of PBK/TOPK predicted the metastatic capability of tumours, and could serve as a significant prognostic predictor in lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 91%
“…These results are similar to those reported by Shih et al . Wei et al . found that overexpression of PBK/TOPK predicted the metastatic capability of tumours, and could serve as a significant prognostic predictor in lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, TOPK and mutant p53 were demonstrated to be independent prognostic factors in lung adenocarcinoma. These observations are partly consistent with the primary findings that patients with TOPK overexpression had a significantly poorer prognosis in stage I lung adenocarcinoma [16]. Zlobec and colleagues [18] also found that TOPK was a valuable prognostic factor in colorectal cancer.…”
Section: Discussionsupporting
confidence: 53%
“…For example, TOPK is involved with highly proliferative cells and tissues and is highly expressed in many types of tumors such as lymphoma, leukemia, breast cancer, Ewing sarcoma, and colorectal cancer [6][7][8][9][10]. High TOPK expression can promote cell proliferation [11][12][13] and prevent apoptosis [14,15] and is associated with a poor prognosis [16][17][18][19]. Moreover, TOPK expression may play an important role in the progress of cytokinesis and inflammation [20][21][22].…”
Section: Introductionmentioning
confidence: 97%
“…Overexpression of PBK has been associated with increased tumorigenicity and clinical lethality of various cancers [3,9,10,12,37]. Future experiments are also needed to further investigate the relationship between the levels of PBK protein and PBK mitotic phosphorylation in cancer patient samples.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PBK overexpression is sufficient to transform mouse epidermal cells [11] and is strongly associated with patient survival and tumor grade [3,9,12]. Several studies have shown that PBK knockdown decreases cell viability and proliferation [7,11,1316] as well as suppressing the cologenic potential of cancer cells [7,10,11,15]. …”
Section: Introductionmentioning
confidence: 99%